Longitudinal increases in mitochondrial DNA levels in blood cells are associated with survival in critically ill patients - Côté, Hélène CF (BioMed Central, 2007)
BACKGROUND: Mitochondrial dysfunction may be causally related to the pathogenesis of organ failure in critically ill patients. Decreased mitochondrial DNA (mtDNA) levels have been associated with mitochondrial dysfunction and were investigated here in relation to short-term (31-day) survival. METHODS: This was a prospective longitudinal cohort study of 28 mechanically ventilated critically ill adults admitted to a single center tertiary care intensive care unit (ICU) with hypotension secondary to cardiogenic (N = 13), septic (N = 14) or hypovolemic (N = 1) disease processes. Clinical data and blood were collected at baseline and patients were followed until they expired or left the ICU. Blood was collected every Monday, Wednesday and Friday, and the buffycoat relative mtDNA/nuclear DNA (nDNA) ratio was determined. An archived pool of healthy controls was also studied. RESULTS: At baseline, the patients' mtDNA/nDNA ratio was 30% lower than a pool of 24 healthy controls (0.76 versus 1.09) and was not different between short-term survivors and non-survivors (0.74 ± 0.05 (N = 16) versus 0.79 ± 0.06 (N = 12), p = 0.49). By day 4, the percent mtDNA/nDNA change from baseline in survivors was significantly different from that in non-survivors (+29.5% versus -5.7%, p = 0.03). It also tended to be higher in survivors at last measurement (+38.4% versus +7.1%, p = 0.06). There was a weak correlation between within patient mtDNA/nDNA and platelet count (r = 0.20, p = 0.03) but not with Sequential Organ Failure Assessment (SOFA) scores (r = 0.12, p = 0.23). The mtDNA associations remained after adjustment for platelet. CONCLUSION: Blood mtDNA levels appeared initially low, increased over time in patients who ultimately survived, and remained low in those who did not. This is consistent with mitochondrial recovery being associated with survival and warrants further investigation as a marker of mitochondrial alterations and outcome in critical illness.